Correlation between stress and primary dysmenorrhea at SMAN 4 Kediri - Putri, Diana Rahmatul; Wijayanti, L.A; Titisari, Ira (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: The physiological disorder experienced by most women in Indonesia every month is primary dysmenorrhea (60-70%). The incidence of primary dysmenorrhea was experienced by female students at SMAN 4 Kediri City, as many as (90.8%) of all female students. One factor is stress. Objective: Determine the relationship between stress and the incidence of primary dysmenorrhea at SMAN 4 Kediri City. Methods: This research used the Analytical research design correlation with a cross-sectional approach, a population of 258 students, and a simple random sampling with a sample of 39 female students. The instrument used was questionnaires, with Spearman rank correlation analysis. Result: The results of this study were moderate stress 28.2% and moderate pain dysmenorrhea 53.8%. Statistical tests showed the correlation coefficient of Spearman rank sig value was 0.030; there was a significant relationship with a reasonably strong relationship strength of 0.347. Stress is the cause of dysmenorrhea to prevent dysmenorrhea can be minimized by preventing stress. Conclusion: the higher the stress, the higher the risk of dysmenorrhea in female students at SMAN 4 Kediri City. The higher the stress level experienced by female students, the greater their risk of experiencing dysmenorrhea (menstrual pain). This suggests that psychological factors such as stress can affect physical health conditions, particularly related to menstrual disorders in adolescent girls. To reduce the risk of dysmenorrhea, it is important to pay attention to stress management in students.